P190 Attitudes of health care professionals towards smoking cessation. (16th November 2010) - Pearce, S; Maycock, J; McCauley, C; Nazareth, D; Stockton, P
Abstract : Background: NICE (UK) recommends that all healthcare professionals (HCPs) refer patients who would like to stop smoking to an NHS Stop Smoking Service (SSS).1 This study explores attitudes of HCPs and factors that may contribute to a low referral rate to SSS. Methods: 164 HCPs (83 doctors, 72 nurses, 9 pharmacists) completed a structured questionnaire exploring reasons as to why they would not refer to smoking cessation services. Results: Smoking cessation was considered to be an important health issue for 95% of respondents, however only 51% routinely asked smokers if they wanted to quit. 37% were not familiar with smoking cessation guidelines (local or national). 40% supported a formal referral system involving a GP and 55% would like more training. The main reasons for NOT referring to SSS are outlined below. Conclusions: The vast majority of HCPs considered smoking cessation to be an important issue. However, a significant proportion of HCPs were unaware of local/national guidelines. This appears tobe a significant barrier to the referral of patients to SSS. Most HCPs would like further targeted training and information. Since this survey the Trust has modified the generic Trust Admission Proforma to prompt HCPs to consider referring to SSS. Teaching sessions have been introduced for HCPs to enable them to deliver accurate stop smoking information to smokers.